Funcionarios de la UNED. (UNED, 2024)
Aparece Angela L. Benavides Mora - Proveeduría, Celedonio Ramírez Ramírez - Rector, Lyra Morera Salas - Centro Universitario de Alajuela, Álvaro Aviles Vargas - Director Administrativo en el parqueo del edificio A